APPLICATION OF MEDICAL AND HYGIENIC AGENTS IN PREVENTION OF LAMENESS AND TREATMENT OF HOOF DISEASES IN COWS - Semenov Vladimir Grigoryevich; Baimukanov Dastanbek Asylbekovich; Alentayev Aleidar Saldarovich; Tikhonov Anatoly Sergeevich; Mikhailova Renata Vasilievna; Chuchulin Alexey Valerievich (Scientific Journal of Pedagogy and Economics, 2020)
Despite the wide range of scientific research on the prevention of lameness and the treatment of hoof diseases of cattle, production trials and implemented treatment methods (antibiotics, sulfonamides, enzymes, immunomodulators, hormones, mud therapy, phyto, magneto, electrotherapy, etc.), many of them are insufficiently effective, expensive, inaccessible or labor-intensive, therefore they cannot be used in dairy farms. The use of antibacterial agents not only did not solve the problems existing in the industry, but also led to the emergence of antibiotic-resistant microbial flora, which put forward new challenges for veterinary science and practice. Under the influence of these preparations, many clinical symptoms and the clinical course of diseases have changed their character, the microbial landscape has changed. Diseases of the hooves are accompanied by lameness and lodging, a decrease in fatness, cows are not bulling for a long time, dryness increases, breeding bulls cannot be used in a random company, which leads to economic damage, therefore the development of affordable and effective means of preventing and treating diseases of hooves in cows is relevant in modern veterinary science and practice. It was established that the treatment of hooves affected by digital dermatitis with medical and hygienic means against the background of intramuscular injection of biological preparation to cows activates hematopoiesis. We have tested the medical and hygienic product Espuarol-Gel with a dermatotropic effect and adhesive properties to soft tissues and hooves based on the chelate complex of lanthanide salts in the prevention of lameness and therapy of hoof diseases of cows. It was found that Espuarol-Gel has a more pronounced health-promoting effect in comparison with previously tested agents: CuSO4, Solka, and Espuarol-Sin, providing a bactericidal effect on causative agents of digital dermatitis, expressed in a decrease in the total group score for the state of the limbs, the total lameness score and total diameter of lesions. The scientific and practical justification of the practicability of the use of the Prevention-N-E biological preparation in the system of measures for the prevention of lameness and treatment of hoof diseases in cows is given. It was found that trimming the hooves of cows and treating them with CuSO4, Solka, Espuarol-Sin, and Espuarol-Gel against the background of the intramuscular injection of the Prevention-N-E activates the hematological profile of nonspecific resistance of the body, prevents gynecological diseases in the labor and postpartum period implements reproductive and productive qualities.